Chiral symmetry breaking and the quark bilinear condensate in large-N QCD. (4th October 2022) - Sato, Ryosuke
Abstract: We discuss spontaneous chiral symmetry breaking and the quark bilinear condensate in large- Nc quantum chromodynamics (QCD). It is known that the existence of the η′ meson is implied in large- Nc QCD, as pointed out by Witten[27 ] and Veneziano[28 ]. First, we show that the existence of η′ and the Ward–Takahashi identities implies the existence of Nambu–Goldstone bosons from chiral symmetry breaking SU ( Nf ) L × SU ( Nf ) R → SU ( Nf ) V . Second, we show that a QCD inequality implies a non-zero lower bound on the quark bilinear condensate.